Formação de interlocutores da comunidade para interação com usuários de Comunicação Alternativa com autismo - Evaristo, Fabiana Lacerda (Universidade Federal de São Carlos, 2019)
Alternative Communication means and strategies are useful tools so that students with non-verbal disabilities to socialize in different environments. This research has objective to elaborate, implement and evaluate a program of formation of communication partners in the community for non-verbal users of alternative communication with autism. The specific objectives were: a) form communication partners to interact with users of Alternative Communication; and b) to evaluate the effects of the implementation of the Alternative Communication Program with users with autism in different environments and with different interlocutors. The study included four participants with autism, four family participants and four participants from the community. Data were collected in a medium-sized municipality and another small municipality, both located in the state of São Paulo in several environments frequented by participants with autism, such as their residence and general trade. A intermittent multiple baseline design cross subjects and environments was used in this research. Eight instruments were used to collect the data: 1) semi-structured interview script for parents / family; 2) a semi-structured interview script for the communication partners; 3) list of participants' interests with autism; 4) daily observation protocol; 5) post intervention questionnaire on the use of alternative communication for the communications partners ; 6) protocol of registration of the social interaction of CA users with community communication partners;7) protocol recording the interaction of community communications partners with CA users; and 8) social validity questionnaire. Communication partners training was the first step of research data collection of the research in which the teaching procedures were implemented with the users with TEA, at which point these procedures were filmed for further analysis. Participants with autism underwent initial assessments, corresponding to baseline sessions, and then intervention was initiated, after baseline stability check. All sessions were performed within the routine in which the participant is inserted. After 13 months of application of the program, a questionnaire was collected with the communication partners, in order to observe if CA users acquired communicative skills in the different environments after using the alternative communication, as well as to help them to expand the alternative communication program at home. The results show that from the training program with the community communication partners with the CA users participants demostrated satisfactory development and their communication skills improved with different people, according to their needs and the number of communication partners has been increased.
Program of formation of communication partners for in the community for interaction with users of Alternative Communication with autism
Keywords: Educação especial; Interlocutor; Comunicação alternativa; Transtorno do espectro autista; Special education; Communication partners; Alternative communication; Autism spectrum disorder; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM